Polysiloxane particles and light modulation laminate
By using polysiloxane particles, which have high-precision gap control capabilities under high temperature environments, the problems of poor gap control and substrate damage in existing resin particles at high temperatures are solved, and the transmittance uniformity of the dimming laminate and the protection of the substrate are achieved.
Patent Information
- Application Number
- CN202380054422.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-20
- Filing Date
- 2023-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
The existing resin particles become soft and prone to breaking or thermal expansion under high temperature environments, resulting in poor gap control effect and may damage the substrate, resulting in uneven transmittance of the dimming laminate and damage to the substrate.
Polysiloxane particles are used, which contain a polysiloxane particle body and a plurality of fillers, and the ratio of the 10% K value at 90°C to the 10% K value at 25°C is 0.90 or more, ensuring that the gap between the substrates can be controlled with high precision in a high temperature environment.
The gap between the substrates is controlled with high precision in a high temperature environment, and the transmittance deviation of the dimming laminate is suppressed, and damage to the substrate is avoided.
Smart Images

Figure CN119631016A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to polysiloxane particles and a light-adjusting laminate using the polysiloxane particles. Background Art
[0002] Dimming materials such as dimming glass and dimming film are materials that have the property of changing light transmittance depending on whether an electric field is applied and can adjust the amount of incident light. In addition, according to the mechanism that changes the light transmittance, the dimming material method is roughly divided into SPD (Suspended Particle Device) method, PDLC (Polymer Dispersed Liquid Crystal) method and GHLC (Guest-Host Liquid Crystal) method.
[0003] The SPD method is a method of dispersing a light regulating suspension in a resin matrix. The light regulating suspension contains light regulating particles. The light regulating particles are capable of responding to an electric field. In the SPD method, when no electric field is applied, the light regulating particles dispersed in the light regulating suspension absorb, scatter or reflect light due to Brownian motion, so that the incident light does not pass through the dimming material. When an electric field is applied, the light regulating particles are polarized and arranged in a direction parallel to the electric field, so that the incident light passes through the dimming material. In this way, in the SPD method, the light transmittance can be adjusted by utilizing the polarization orientation of the light regulating particles.
[0004] The PDLC method is a method of dispersing liquid crystals in a resin matrix. As forms of the PDLC method, there are forms in which liquid crystals and resin matrices are dispersed as a continuous phase, and forms in which liquid crystals are dispersed in a resin matrix as liquid crystal capsules. When no electric field is applied, the orientation of the liquid crystal molecules is uneven, so due to the difference in refractive index between the resin matrix and the liquid crystal, the incident light is scattered in the dimming material, and an opaque state is observed. When an electric field is applied, the liquid crystal molecules are arranged in a direction parallel to the electric field. At this time, by making the refractive index of the resin matrix equal to that of the liquid crystal, the incident light can be transmitted through the dimming material, and a transparent state is observed. In this way, in the PDLC method, the light transmittance is adjusted by utilizing the molecular orientation of the liquid crystal.
[0005] The GHLC method is a method in which a dichroic dye is dispersed in liquid crystal. In the GHLC method, the orientation direction of the dichroic dye and liquid crystal can be changed between a state in which an electric field is not applied and a state in which an electric field is applied, and the light transmittance can be adjusted.
[0006] When a dimming laminate is prepared using a dimming material, a spacer is sometimes used to control the gap between two substrates. As the spacer, resin particles and the like can be cited. As an example of such resin particles, the following patent document 1 discloses a polymer particle comprising a constituent component derived from a monomer component, wherein the monomer component comprises a styrene-based monomer and an alkyl (meth)acrylate having an alkyl carbon number of 1 to 18.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2022-079565 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] In the case of the conventional resin particles described in Patent Document 1, when the resin particles are used as spacers, the resin particles become soft and easily break or thermally expand in a high temperature environment, and thus the gap control effect may not be fully exerted. When such resin particles are used as spacer particles for dimming laminates, the thickness of the dimming layer in the obtained dimming laminate is uneven, resulting in a technical problem that the transmittance of the dimming layer is biased.
[0012] In addition, in order to improve the gap control effect of the spacer, when using inorganic particles with low temperature dependence and high dimensional stability, the inorganic particles sometimes damage the substrate (adherent). In particular, in a dimming film using a film as a substrate, when the particles are used as a gap material, since the particles are hard, there is a technical problem that the particles are easy to damage the substrate during the manufacture or use of the dimming film. In the dimming film, if the substrate is damaged, abnormal orientation of the liquid crystal sometimes occurs.
[0013] The object of the present invention is to provide polysiloxane particles capable of controlling the gap between substrates with high precision even in a high temperature environment, suppressing the deviation of the transmittance of the obtained dimming laminate, and suppressing damage to the substrate. In addition, the object of the present invention is to provide a dimming laminate capable of controlling the gap between substrates with high precision even in a high temperature environment, suppressing the deviation of the transmittance of the obtained dimming laminate, and suppressing damage to the substrate.
[0014] Technical means to solve technical problems
[0015] This specification discloses the following polysiloxane particles and a light-adjusting laminate.
[0016] Item 1. A polysiloxane particle comprising a polysiloxane particle body and a plurality of fillers, at least one of the plurality of fillers being present inside the polysiloxane particle body, wherein the ratio of the 10% K value at 90° C. to the 10% K value at 25° C. of the polysiloxane particle is 0.90 or more.
[0017] Item 2. The polysiloxane particles according to Item 1, wherein the 10% K value at 25° C. is 2000 N / mm 2 the following.
[0018] Item 3. The polysiloxane particles according to Item 1 or 2, wherein the 10% K value at 90° C. is 1800 N / mm 2 the following.
[0019] Item 4. The polysiloxane particles according to any one of Items 1 to 3, wherein the polysiloxane particles have a compression recovery rate at 25° C. of 91% or less.
[0020] Item 5. The polysiloxane particles according to any one of Items 1 to 4, wherein the particle size is 30 μm or less.
[0021] Item 6. The polysiloxane particles according to any one of Items 1 to 5, wherein the CV value of the particle size is 15% or less.
[0022] Item 7. The polysiloxane particles according to any one of Items 1 to 6, wherein the polysiloxane particles have a visible light transmittance of 10% or less.
[0023] Item 8. The polysiloxane particles according to any one of Items 1 to 7, wherein the filler is a colorant.
[0024] Item 9. The polysiloxane particles according to Item 8, wherein the colorant is inorganic particles, a pigment, or a dye.
[0025] Item 10. The polysiloxane particles according to Item 8 or 9, wherein the colorant is a white colorant or a black colorant.
[0026] Item 11. The polysiloxane particles according to any one of Items 1 to 10, wherein a content of the filler is 0.1% by weight or more and 30% by weight or less in 100% by weight of the polysiloxane particles.
[0027] Item 12. The polysiloxane particles according to Item 11, wherein a content of the filler is 3.0% by weight or more and 10% by weight or less in 100% by weight of the polysiloxane particles.
[0028] Item 13. A light-adjusting laminate comprising a first substrate, a second substrate, and a light-adjusting layer disposed between the first substrate and the second substrate, wherein the light-adjusting layer comprises the polysiloxane particles according to any one of Items 1 to 12.
[0029] Effects of the Invention
[0030] The polysiloxane particles of the present invention include a polysiloxane particle body and a plurality of fillers, at least one of the plurality of fillers is present inside the polysiloxane particle body, and the ratio of the 10% K value of the polysiloxane particles at 90° C. to the 10% K value at 25° C. is 0.90 or more. In the polysiloxane particles of the present invention, due to the above-mentioned structure, the gap between the substrates can be controlled with high precision even in a high temperature environment, the transmittance variation of the obtained dimming laminated body can be suppressed, and damage to the substrate can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] [ Figure 1 ] Figure 1 This is a cross-sectional view schematically showing the polysiloxane particles according to the first embodiment of the present invention.
[0032] [ Figure 2 ] Figure 2 This is a cross-sectional view schematically showing the polysiloxane particles according to the second embodiment of the present invention.
[0033] [ Figure 3 ] Figure 3 This is a cross-sectional view schematically showing a PDLC-type light-adjusting laminated body including the polysiloxane particles according to the first embodiment of the present invention.
[0034] [ Figure 4 ] Figure 4 This is a cross-sectional view schematically showing an SPD-type light-adjusting laminated body including the polysiloxane particles according to the first embodiment of the present invention.
[0035] [ Figure 5 ] Figure 5 This is a cross-sectional view schematically showing a GHLC-type light-adjusting laminated body including the polysiloxane particles according to the first embodiment of the present invention. DETAILED DESCRIPTION
[0036] Hereinafter, the present invention will be described in detail. It should be noted that, in the present specification, for example, "(meth)acryloyloxy" refers to one or both of "acryloyloxy" and "methacryloyloxy", and "(meth)acrylic" refers to one or both of "acrylic" and "methacrylic".
[0037] (Polysiloxane particles)
[0038] The polysiloxane particles of the present invention include a polysiloxane particle body and a plurality of fillers. In the polysiloxane particles of the present invention, at least one of the plurality of fillers is present inside the polysiloxane particle body. In the polysiloxane particles of the present invention, a ratio of a 10% K value at 90°C to a 10% K value at 25°C is 0.90 or more.
[0039] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings.
[0040] Figure 1 This is a cross-sectional view schematically showing the polysiloxane particles according to the first embodiment of the present invention.
[0041] Figure 1 The polysiloxane particle 1 shown includes a polysiloxane particle main body 2 and a plurality of fillers 3. In the polysiloxane particle 1, all of the plurality of fillers 3 are present inside the polysiloxane particle main body 2. In the polysiloxane particle 1, the plurality of fillers 3 are dispersed in the polysiloxane particle main body 2.
[0042] No matter which filler among the multiple fillers 3 of the polysiloxane particle 1 is observed, the entire filler is present inside the polysiloxane particle body 2. When any one of the fillers in the polysiloxane particle is observed, the filler may be in the following states. In the polysiloxane particle, the entirety of any one of the fillers may be present inside the polysiloxane particle body, or a portion of any one of the fillers may be present inside the polysiloxane particle body. A portion of any one of the fillers may be present outside the polysiloxane particle body.
[0043] Figure 2 This is a cross-sectional view schematically showing the polysiloxane particles according to the second embodiment of the present invention.
[0044] Figure 2 The polysiloxane particle 1A shown includes a polysiloxane particle body 2 and a plurality of fillers 3A. In the polysiloxane particle 1A, at least one of the plurality of fillers 3A is present inside the polysiloxane particle body 2. In the polysiloxane particle 1A, a portion of the plurality of fillers 3A is present inside the polysiloxane particle body 2, and a portion of the plurality of fillers 3A is present outside the polysiloxane particle body 2. In the polysiloxane particle 1A, a plurality of fillers 3A are present inside and outside the polysiloxane particle body 2. In the polysiloxane particle 1A, a plurality of fillers 3A are present inside the polysiloxane particle body 2 and on the outer surface of the polysiloxane particle body 2. In the polysiloxane particle 1A, a portion of the plurality of fillers 3A is arranged outside the polysiloxane particle body 2. In the polysiloxane particle 1A, a plurality of fillers 3A are dispersed in the polysiloxane particle body 2.
[0045] The polysiloxane particle 1A includes fillers 3A that are entirely present inside the polysiloxane particle body 2, fillers 3A that are partially present outside the polysiloxane particle body 2 (fillers 3A that are partially present inside the polysiloxane particle body 2), and fillers 3A that are entirely present outside the polysiloxane particle body 2.
[0046] In the polysiloxane particles, the ratio of the 10% K value at 90°C to the 10% K value at 25°C (10% K value at 90°C / 10% K value at 25°C) is preferably 0.93 or more, more preferably 0.95 or more, and even more preferably 0.99 or more. When the ratio (10% K value at 90°C / 10% K value at 25°C) is above the lower limit, the gap between the substrates can be controlled with further high accuracy even in a high temperature environment, and damage to the substrates can be further suppressed. In the polysiloxane particles, the ratio of the 10% K value at 90°C to the 10% K value at 25°C (10% K value at 90°C / 10% K value at 25°C) is preferably 1.10 or less, more preferably 1.05 or less, and even more preferably 1.00 or less. When the ratio (10% K value at 90°C / 10% K value at 25°C) is below the upper limit, the gap between the substrates can be controlled with further high accuracy even in a high temperature environment, and damage to the substrates can be further suppressed. The ratio (10% K value at 90°C / 10% K value at 25°C) is preferably above the lower limit and below the upper limit.
[0047] As a method for adjusting the ratio (10% K value at 90°C / 10% K value at 25°C) to a preferred range, there are methods of adjusting the content of filler and adjusting the content of the polysiloxane particles. 29 The method of calculating the ratio of siloxane skeleton by Si-NMR spectrum, etc.
[0048] The 10% K value at 90°C is preferably 2000 N / mm 2 Below, more preferably 1800N / mm 2 Below, more preferably 1000 N / mm 2 Below, particularly preferably 100 N / mm 2 The 10% K value at 90°C is also preferably 1800 N / mm 2 Below, preferably 1620N / mm 2 Below, preferably 900 N / mm 2 Below, preferably 90 N / mm 2 When the 10% K value at 90°C is below the upper limit, the gap between the substrates can be controlled with higher precision even in a high temperature environment, and damage to the substrates can be further suppressed. The 10% K value at 90°C is preferably 1 N / mm2 More preferably 5N / mm 2 More than, more preferably 10N / mm 2 The 10% K value at 90°C is also preferably 0.9 N / mm 2 Above, preferably 4.5 N / mm 2 Above, preferably 9N / mm 2 When the 10% K value at 90°C is greater than the lower limit, the gap between the substrates can be controlled with greater precision even in a high temperature environment, and damage to the substrates can be further suppressed. The 10% K value at 90°C is preferably greater than the lower limit and less than the upper limit.
[0049] The 10% K value at 25°C is preferably 2000 N / mm 2 Below, more preferably 1800N / mm 2 Below, more preferably 1000 N / mm 2 Below, particularly preferably 100 N / mm 2 The 10% K value at 25°C is also preferably 2222 N / mm 2 Below, preferably 2000 N / mm 2 Below, preferably 1111N / mm 2 Below, preferably 111 N / mm 2 When the 10% K value at 25°C is below the upper limit, the gap between the substrates can be controlled with higher precision, and damage to the substrates can be further suppressed. The 10% K value at 25°C is preferably 1 N / mm 2 More preferably 5N / mm 2 More than, more preferably 10N / mm 2 The 10% K value at 25°C is also preferably 1.11 N / mm 2 Above, preferably 5.56 N / mm 2 Above, preferably 11.11 N / mm 2 When the 10% K value at 25°C is greater than or equal to the lower limit, the gap between the substrates can be controlled with greater accuracy, and damage to the substrates can be further suppressed. The 10% K value at 25°C is preferably greater than or equal to the lower limit and less than or equal to the upper limit.
[0050] The 10% K value at 25°C and 90°C can be measured as follows. Using a micro compression tester, compress the polysiloxane particles at 25°C or 90°C on the smooth indenter end face of a cylinder (diameter 50 μm, made of diamond) under the conditions of a maximum test load of 20 mN for 60 seconds. Measure the load value (N) and compression displacement (mm) at this time. Based on the measured values obtained, the 10% K value can be calculated using the following formula. As the micro compression tester, for example, "FISCHERSCOPE H-100" manufactured by FISCHER Corporation is used.
[0051] 10% K value (N / mm 2 )=(3 / 2 1 / 2 )·F·S -3 / 2 ·R -1 / 2
[0052] F: Load value when polysiloxane particles are compressed to 10% (N)
[0053] S: Compression displacement of polysiloxane particles when they are compressed by 10% (mm)
[0054] R: radius of polysiloxane particles (mm)
[0055] The compression recovery rate of the polysiloxane particles at 25°C is preferably 91% or less, more preferably 90% or less, and further preferably 88% or less. The compression recovery rate of the polysiloxane particles at 25°C may be 80% or less. If the compression recovery rate of the polysiloxane particles at 25°C is below the upper limit, the gap between the substrates can be controlled with higher accuracy. The compression recovery rate of the polysiloxane particles at 25°C is preferably 70% or more, more preferably 75% or more, and further preferably 80% or more. If the compression recovery rate of the polysiloxane particles at 25°C is above the lower limit, the gap between the substrates can be controlled with higher accuracy. The compression recovery rate of the polysiloxane particles at 25°C is preferably above the lower limit and below the upper limit.
[0056] The compression recovery rate of the polysiloxane particles at 25° C. can be measured as follows.
[0057] Polysiloxane particles are spread on a sample stand. For one of the spread polysiloxane particles, a micro compression tester is used. A load is applied to the smooth indenter end face of a cylinder (diameter 50 μm, made of diamond) at 25°C toward the center of the polysiloxane particle with an origin load value of 1.0 mN and a reversal load value of 10 mN. The recovery behavior after the load is removed is analyzed, and the compression recovery rate is derived. The load-compression displacement during this period is measured, and the compression recovery rate can be calculated by the following formula. It should be noted that the load speed is 0.33 mN / second. As the micro compression tester, for example, "FISCHER SCOPE H-100" manufactured by FISCHER Company is used.
[0058] Compression recovery rate (%) = [L2 / L1] × 100
[0059] L1: Compressive displacement from the load value at the origin when the load is applied to the reverse load value
[0060] L2: Unloading displacement from the reverse load value when releasing the load to the load value at the origin
[0061] The particle size of the polysiloxane particles is preferably 100 μm or less, more preferably 50 μm or less, and further preferably 30 μm or less. If the particle size of the polysiloxane particles is below the upper limit, the practicality can be improved and the gap between the substrates can be more appropriate. The particle size of the polysiloxane particles is preferably 3 μm or more, more preferably 5 μm or more, and further preferably 8 μm or more. If the particle size of the polysiloxane particles is above the lower limit, the practicality can be improved and the gap between the substrates can be more appropriate. The particle size of the polysiloxane particles is preferably above the lower limit and below the upper limit.
[0062] The particle size of the polysiloxane particles refers to the diameter when the polysiloxane particles are in a true spherical shape, and refers to the diameter when the polysiloxane particles are in a shape other than a true spherical shape, assuming a true sphere of a volume equivalent to the particle size.
[0063] The particle size of the polysiloxane particles is preferably an average particle size, more preferably a number average particle size. The particle size of the polysiloxane particles can be measured using any particle size distribution measuring device. For example, a particle size distribution measuring device that utilizes the principles of laser scattering, resistance value change, image analysis after shooting, etc. can be used for measurement. More specifically, as a method for measuring the particle size of polysiloxane particles, a method of using a particle size distribution measuring device ("Multisizer 4" manufactured by Beckman Coulter) to measure the particle size of about 100,000 polysiloxane particles and calculate the average value can be cited.
[0064] The coefficient of variation (CV value) of the particle size of the polysiloxane particles is preferably 15% or less, more preferably 10% or less, and further preferably 8% or less. If the coefficient of variation (CV value) of the particle size of the polysiloxane particles is below the upper limit, the gap between the substrates can be controlled with higher accuracy. The coefficient of variation (CV value) of the particle size of the polysiloxane particles is preferably 0% or more. The coefficient of variation (CV value) of the particle size of the polysiloxane particles is preferably above the lower limit and below the upper limit.
[0065] The coefficient of variation (CV value) of the particle size of the polysiloxane particles can be measured as follows.
[0066] CV value (%) = (ρ / Dn) × 100
[0067] ρ: standard deviation of the particle size of the polysiloxane particles
[0068] Dn: average particle size of the polysiloxane particles
[0069] The shape of the polysiloxane particles is not particularly limited, and the polysiloxane particles may be spherical, may be other than spherical, may be flat, and the like.
[0070] From the viewpoint of controlling the gap between substrates with higher precision, the aspect ratio of the polysiloxane particles is preferably 1.5 or less, more preferably 1.3 or less. The lower limit of the aspect ratio of the polysiloxane particles is not particularly limited. The aspect ratio of the polysiloxane particles may be 1.0 or more, or 1.1 or more. The aspect ratio represents the major diameter / minor diameter. The aspect ratio is preferably obtained as follows: observe 10 arbitrary polysiloxane particles using an electron microscope or an optical microscope, take the maximum diameter and the minimum diameter as the major diameter and the minor diameter, respectively, obtain the major diameter / minor diameter of each polysiloxane particle, calculate the average value of the major diameter / minor diameter of the 10 polysiloxane particles, and thereby obtain.
[0071] From the viewpoint of improving the operability of the obtained dimming material and dimming laminate, the specific gravity of the polysiloxane particles is preferably 1.5 or less, more preferably 1.4 or less, and further preferably 1.3 or less. The specific gravity of the polysiloxane particles may be 0.9 or more, or 1.0 or more.
[0072] From the viewpoint of further suppressing the deviation of the transmittance of the obtained dimming laminate, the visible light transmittance of the polysiloxane particles is preferably 10% or less, more preferably 5% or less, further preferably 1% or less, further preferably 0.1% or less, and particularly preferably 0.05% or less. The lower limit of the visible light transmittance of the polysiloxane particles is not particularly limited. The visible light transmittance of the polysiloxane particles may be 0% or more, or 0.05% or more.
[0073] The visible light transmittance of the polysiloxane particles can be measured as follows: a plate-shaped sample having the same composition as the polysiloxane particles can be prepared, and the visible light transmittance can be measured by spectrophotometry according to ISO13837:2008. Alternatively, the visible light transmittance can be measured by a method according to JIS K6714.
[0074] The polysiloxane particles are suitable for use as gap materials (spacers). The polysiloxane particles are preferably used as gap materials (spacers). As the gap materials (spacers), spacers for liquid crystal display elements, spacers for gap control, spacers for stress relaxation, and spacers for dimming laminates can be cited. The gap control spacer can be used for: gap control of laminated chips, electronic component devices, and gap control of optical components for ensuring the smoothness of the glass surface and the thickness of the adhesive layer to ensure the smoothness of the glass surface and the thickness of the adhesive layer. The stress relaxation spacer can be used for stress relaxation of sensor chips, etc., and stress relaxation of the connecting portion connecting two connection object components. As the sensor chip, for example, a semiconductor sensor chip can be cited. In addition, when the polysiloxane particles are used as gap materials (spacers), they can be fully contacted with the connection object components, etc., and a sufficient gap control effect can be obtained.
[0075] The polysiloxane particles are preferably used as spacers for liquid crystal display elements, and are preferably used for peripheral sealants for liquid crystal display elements. In the peripheral sealant for liquid crystal display elements, the polysiloxane particles preferably function as spacers. The polysiloxane particles may not be spacers for liquid crystal display elements, but may be spacers for gap control, spacers for stress relaxation, or spacers for dimming laminates.
[0076] In addition, when the polysiloxane particles are used as spacers for dimming materials, the dimming materials are preferably dimming glass and dimming film. The dimming materials such as dimming glass and dimming film are preferably used for window glass or partitions of vehicles. As the vehicles, vehicles, ships and airplanes can be cited. The dimming materials such as dimming glass and dimming film are preferably used for window glass or partitions of vehicles such as vehicles, ships and airplanes. The dimming material is preferably a window glass or partition, and more preferably a window glass or partition of vehicles such as vehicles, ships and airplanes. The dimming material can be a window glass of vehicles, ships and airplanes, or a partition. The vehicle is preferably a transportation mechanism. The partition can also be a component that is arranged between the seats of the vehicle and separates the seats. The partition can also be a partition used in a state where the main surfaces on both sides are in contact with the atmosphere.
[0077] Hereinafter, each component of the polysiloxane particles will be described in detail.
[0078] <Polysilicone Particle Main Body>
[0079] The polysiloxane particles include a polysiloxane particle body. The polysiloxane particles and the polysiloxane particle body preferably include a polysiloxane resin. The polysiloxane resin has a siloxane skeleton (siloxane bond).
[0080] From the viewpoint of controlling the gap with higher precision in a wide temperature range, the material of the main body of the polysiloxane particles is preferably an organopolysiloxane, and is also preferably a silanolate. The organopolysiloxane and the silanolate may be used alone or in combination of two or more.
[0081] From the viewpoint of making it easier to adjust the ratio (10% K value at 90°C / 10% K value at 25°C) to a preferred range, the polysiloxane particles are 29 The proportion of the siloxane skeleton calculated by Si-NMR spectrum is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more. 29 The upper limit of the proportion of the siloxane skeleton calculated by Si-NMR spectrum is not particularly limited. 29 The ratio of the siloxane skeleton calculated from the Si-NMR spectrum may be 100% or less, may be less than 100%, may be 99% or less, or may be 90% or less.
[0082] The ratio of the siloxane skeleton can be measured as follows: for the polysiloxane particles, nuclear magnetic resonance analysis (NMR) is performed using an NMR spectrometer (for example, "JNM-ECX400" manufactured by Jeol Resonance Co., Ltd.), and the ratio of the integrated value of the peak area of the siloxane skeleton to the integrated value of the peak area of all signals (100%) is calculated.
[0083] From the viewpoint of controlling the gap with higher accuracy, the silanolate preferably includes silanolate A represented by the following formula (1A) or silanolate B represented by the following formula (1B). The silanolate may include silanolate A represented by the following formula (1A) or silanolate B represented by the following formula (1B).
[0084] Si(R1) n (OR2) 4-n ...(1A)
[0085] In the formula (1A), R1 represents a hydrogen atom, a phenyl group or an alkyl group having 1 to 30 carbon atoms, R2 represents an alkyl group having 1 to 6 carbon atoms, and n represents an integer of 0 to 2. When n is 2, multiple R1s may be the same or different. Multiple R2s may be the same or different.
[0086] When R1 in the formula (1A) is an alkyl group having 1 to 30 carbon atoms, examples of R1 include methyl, ethyl, propyl, isopropyl, isobutyl, n-hexyl, cyclohexyl, n-octyl, and n-decyl. The number of carbon atoms in the alkyl group is preferably 10 or less, more preferably 6 or less. It should be noted that the alkyl group includes a cycloalkyl group.
[0087] Examples of R2 in the formula (1A) include methyl, ethyl, n-propyl, isopropyl, n-butyl, and isobutyl.
[0088] Examples of the silane alkoxide A include tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, isopropyltrimethoxysilane, isobutyltrimethoxysilane, cyclohexyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, and diphenyldimethoxysilane. Other silane alkoxides may also be used.
[0089] Si(R1) n (OR2) 4-n ...(1B)
[0090] In the formula (1B), R1 represents a hydrogen atom, a phenyl group, an alkyl group having 1 to 30 carbon atoms, or an organic group having 1 to 30 carbon atoms having a polymerizable double bond, R2 represents an alkyl group having 1 to 6 carbon atoms, and n represents an integer from 0 to 2. When n is 2, multiple R1s may be the same or different. Multiple R2s may be the same or different. At least one R1 is preferably an organic group having 1 to 30 carbon atoms having a polymerizable double bond, more preferably a vinyl group, a styryl group or a (meth)acryloyloxy group, further preferably a vinyl group or a (meth)acryloyloxy group, and particularly preferably a (meth)acryloyloxy group.
[0091] When R1 in the formula (1B) is an alkyl group having 1 to 30 carbon atoms, examples of R1 include methyl, ethyl, propyl, isopropyl, isobutyl, n-hexyl, cyclohexyl, n-octyl, and n-decyl. The number of carbon atoms in the alkyl group is preferably 10 or less, more preferably 6 or less. It should be noted that the alkyl group includes a cycloalkyl group.
[0092] As the polymerizable double bond, a carbon-carbon double bond can be mentioned. When R1 in the formula (1B) is an organic group having 1 to 30 carbon atoms and having a polymerizable double bond, as R1, vinyl, styryl, allyl, isopropenyl, and 3-(meth)acryloyloxyalkyl can be mentioned. As the styryl, para-styryl, o-styryl and m-styryl can be mentioned. As the (meth)acryloyloxyalkyl, (meth)acryloyloxymethyl, (meth)acryloyloxyethyl, and (meth)acryloyloxypropyl can be mentioned. The number of carbon atoms of the organic group having 1 to 30 carbon atoms and having a polymerizable double bond is preferably 2 or more, preferably 30 or less, and more preferably 10 or less.
[0093] Examples of R2 in the formula (1B) include methyl, ethyl, n-propyl, isopropyl, n-butyl, and isobutyl.
[0094] From the viewpoint of controlling the gap with higher accuracy, the silanolate preferably contains dialkoxysilane.
[0095] From the viewpoint of more easily adjusting the particle size, the silanolate preferably includes a silanolate having a polymerizable functional group, and more preferably includes a silanolate having a polymerizable double bond. As the silanolate having a polymerizable double bond, there can be mentioned: vinyl trimethoxysilane, vinyl triethoxysilane, dimethoxymethyl vinyl silane, dimethoxyethyl vinyl silane, diethoxymethyl vinyl silane, diethoxyethyl vinyl silane, ethylmethyl divinyl silane, methyl vinyl dimethoxy silane, ethyl vinyl dimethoxy silane, methyl vinyl diethoxy silane, ethyl vinyl diethoxy silane, p-phenyleneditrimethoxysilane, 3-methacryloxypropyl methyl dimethoxy silane, 3-methacryloxypropyl trimethoxy silane, 3-methacryloxypropyl methyl diethoxy silane, 3-methacryloxypropyl triethoxy silane, and 3-acryloxypropyl trimethoxy silane. The silane alkoxide may be a cyclic siloxane or a modified (reactive) silicone oil. Examples of the cyclic siloxane include decamethylcyclopentasiloxane, etc. Examples of the modified silicone oil include single-end modified silicone oil, dual-end silicone oil, and side chain silicone oil.
[0096] Specific methods for producing the polysiloxane particle body include a method of preparing the polysiloxane particle body by pre-condensing the silanolate to obtain an oligomer and then performing a polymerization reaction by suspension polymerization, dispersion polymerization, miniemulsion polymerization, or emulsion polymerization.
[0097] From the viewpoint of further suppressing the variation in transmittance of the obtained light-adjusting laminate, the refractive index of the polysiloxane particle body is preferably 1.39 or more, more preferably 1.40 or more, and is preferably 1.44 or less, more preferably 1.43 or less.
[0098] The refractive index of the polysiloxane particle body can be measured according to JIS K7142:2014 Plastics - Determination of refractive index, method B.
[0099] The particle size of the polysiloxane particle body is preferably 99.8 μm or less, more preferably 49.8 μm or less, and further preferably 29.8 μm or less. If the particle size of the polysiloxane particle body is below the upper limit, the gap between the substrates can be further controlled with high precision, and the damage to the substrate can be further suppressed. The particle size of the polysiloxane particle body is preferably 2.8 μm or more, more preferably 4.8 μm or more, and further preferably 7.8 μm or more. If the particle size of the polysiloxane particle body is above the lower limit, the gap between the substrates can be further controlled with high precision, and the damage to the substrate can be further suppressed. The particle size of the polysiloxane particle body is preferably above the lower limit and below the upper limit.
[0100] The particle size of the polysiloxane particle body refers to the diameter when the polysiloxane particle body is a true sphere, and refers to the diameter when the polysiloxane particle body is a shape other than a true sphere, assuming a true sphere of a volume equivalent thereto.
[0101] The particle size of the polysiloxane particle body is preferably an average particle size, more preferably a number average particle size. The particle size of the polysiloxane particle body can be measured using any particle size distribution measuring device. For example, a particle size distribution measuring device that utilizes principles such as laser scattering, resistance value change, and image analysis after shooting can be used for measurement. More specifically, as a method for measuring the particle size of the polysiloxane particle body, a method of using a particle size distribution measuring device ("Multisize 4" manufactured by Beckman Coulter) to measure the particle size of about 100,000 polysiloxane particle bodies and calculate the average particle size can be cited.
[0102] From the viewpoint of controlling the gap between the substrates with higher precision, the coefficient of variation (CV value) of the particle size of the polysiloxane particle body is preferably 15% or less, more preferably 10% or less, and further preferably 8% or less. The coefficient of variation (CV value) of the particle size of the polysiloxane particle body is preferably 0% or more. The coefficient of variation (CV value) of the particle size of the polysiloxane particle body is preferably above the lower limit and below the upper limit.
[0103] The coefficient of variation (CV value) of the particle size of the polysiloxane particle body can be measured as follows.
[0104] CV value (%) = (ρ / Dn) × 100
[0105] ρ: standard deviation of the particle size of the polysiloxane particles
[0106] Dn: average particle size of the polysiloxane particles
[0107] The shape of the polysiloxane particle body is not particularly limited. The polysiloxane particle body may be spherical, may be a shape other than a spherical shape, may be flat, and the like.
[0108] In 100 wt % of the polysiloxane particles, the content of the polysiloxane particle main body is preferably 80 wt % or more, more preferably 85 wt % or more, further preferably 90 wt % or more, particularly preferably 95 wt % or more, preferably 99.9 wt % or less, more preferably 99 wt % or less, further preferably 98 wt % or less. If the content of the polysiloxane particle main body is above the lower limit and below the upper limit, the gap between the substrates can be controlled with further high precision, and damage to the substrates can be further suppressed.
[0109] In the polysiloxane particle main body 100 weight %, the content of the polysiloxane resin is preferably 80 weight % or more, more preferably 85 weight % or more, further preferably 90 weight % or more, and particularly preferably 95 weight % or more. When the content of the polysiloxane resin is above the lower limit, the gap between the substrates can be controlled with higher accuracy. The upper limit of the content of the polysiloxane resin is not particularly limited. In the polysiloxane particle main body 100 weight %, the content of the polysiloxane resin can be 100 weight % (total amount), can be below 100 weight %, or can be less than 100 weight %.
[0110] <Packing>
[0111] The polysiloxane particles include a plurality of fillers. In the polysiloxane particles, at least one of the plurality of fillers is present inside the polysiloxane particle body.
[0112] In the polysiloxane particles, the filler may be entirely present inside the polysiloxane particle body, a portion of the filler may be present inside the polysiloxane particle body, or a portion of the filler may be present outside the polysiloxane particle body. In the polysiloxane particles, the filler may be entirely present inside the polysiloxane particle body, a portion of the filler may be present inside the polysiloxane particle body, or a portion of the filler may be present outside the polysiloxane particle body.
[0113] In the polysiloxane particles, any one of the fillers may be present entirely inside the polysiloxane particle body, any one of the fillers may be present partially inside the polysiloxane particle body, and any one of the fillers may be present partially outside the polysiloxane particle body. In the polysiloxane particles, any one of the fillers may be present entirely outside the polysiloxane particle body, but at least one of the plurality of fillers may be present inside the polysiloxane particle body.
[0114] A portion of the filler is present in the filler inside the polysiloxane particle body, and the volume of the portion present inside the polysiloxane particles in 100% by volume of the filler is preferably 50% by volume or more, more preferably 60% by volume or more, and further preferably 70% by volume or more. In 100% by volume of the filler, the volume of the portion present inside the polysiloxane particles is preferably 99% by volume or less, more preferably 95% by volume or less, and further preferably 90% by volume or less. If the volume of the portion present inside the polysiloxane particles is above the lower limit and below the upper limit, the filler can be better fixed to the surface of the polysiloxane particle body. The volume of the portion present inside the polysiloxane particles is preferably above the lower limit and below the upper limit.
[0115] From the viewpoint of improving the dispersibility of the polysiloxane particles, the polysiloxane particles preferably contain a mixture of a filler in which a part of the filler is present inside the main body of the polysiloxane particles and a filler in which the entirety of the filler is present inside the polysiloxane particles.
[0116] From the viewpoint of further effectively exerting the effects of the present invention, in the polysiloxane particles, the number of fillers present inside the polysiloxane particles is preferably 70% or more, more preferably 80% or more, further preferably 90% or more, and preferably 100% or less out of the total number of the fillers (100%). It should be noted that when observing one filler, if all or part of the filler is present inside the main body of the polysiloxane particles, the filler is judged to be equivalent to the filler present inside the polysiloxane particles. When observing one filler, if at least part of the filler is present inside the main body of the polysiloxane particles, the filler is judged to be equivalent to the filler present inside the polysiloxane particles. When observing one filler, if the entire filler is not present inside the main body of the polysiloxane particles, the filler is judged not to be equivalent to the filler present inside the polysiloxane particles.
[0117] In the polysiloxane particles, the plurality of fillers may be dispersed inside the polysiloxane particle body or may be unevenly distributed. In order to further suppress damage to the substrate of the obtained dimming laminate, the plurality of fillers in the polysiloxane particles are preferably dispersed inside the polysiloxane particle body.
[0118] Examples of the filler include colorants, alumina, talc, barium titanate, and ferrite.
[0119] From the viewpoint of improving light-shielding properties, the filler is preferably a colorant.
[0120] The colorant may be a white colorant, a black colorant, a red colorant, a blue colorant, or a yellow colorant. From the viewpoint of improving light-shielding properties, the colorant is preferably a white colorant or a black colorant.
[0121] Examples of the colorant include inorganic particles, pigments, and dyes. The colorant may be used alone or in combination of two or more.
[0122] From the viewpoint of improving light-shielding properties, the colorant is preferably inorganic particles, a pigment, a dye, or the like.
[0123] Examples of the inorganic particles include carbon black particles, carbon nanotube particles, titanium black particles, graphene particles, iron oxide particles, zinc oxide particles, calcium carbonate particles, aluminum oxide particles, kaolin particles, calcium silicate particles, magnesium oxide particles, magnesium hydroxide particles, aluminum hydroxide particles, magnesium carbonate particles, talc particles, feldspar powder particles, mica particles, barite particles, barium carbonate particles, titanium oxide particles, silicon dioxide particles, and glass beads. The inorganic particles are preferably carbon black particles or titanium black particles.
[0124] The average particle size of the inorganic particles is preferably 0.01 μm or more, more preferably 0.5 μm or more, preferably 30 μm or less, more preferably 20 μm or less, further preferably 10 μm or less, and particularly preferably 5 μm or less. The average particle size represents the weight average particle size. The average particle size can be measured by a dynamic light scattering method using a light scattering measuring device with a laser as a light source. As the light scattering measuring device, for example, "DLS-6000AL" manufactured by OTSUKA ELECTRONICS Co., Ltd. can be cited.
[0125] Examples of the dye include pyrene-based dyes, aminoketone-based dyes, anthraquinone-based dyes, and azo-based dyes.
[0126] Examples of the pyrene dyes include Solvent Green 5 (CAS 79869-59-3) and Solvent Green 7 (CAS 6358-69-6).
[0127] Examples of the aminoketone dye include Solvent Yellow 98 (CAS 12671-74-8), Solvent Yellow 85 (CAS 12271-01-1), Solvent Red 179 (CAS 8910-94-5), and Solvent Red 135 (CAS 71902-17-5).
[0128] Examples of the anthraquinone dyes include Solvent Yellow 163 (CAS13676091-0), Solvent Red 207 (CAS15958-69-6), Disperse Red 92 (CAS12236-11-2), Solvent Violet 13 (CAS81-48-1), Disperse Violet 31 (CAS6408-72-6), Solvent Blue 97 (CAS61969-44-6), Solvent Blue 45 (CAS37229-23-5), Solvent Blue 104 (CAS116-75-6) and Disperse Blue 214 (CAS104491-84-1).
[0129] Examples of the azo dye include Solvent Yellow 30 (CAS 3321-10-4), Solvent Red 164 (CA S70956-30-8), and Disperse Blue 146 (CAS 88650-91-3).
[0130] The pigment may be an organic pigment or an inorganic pigment. The organic pigment may or may not have a metal atom. The pigment may be a white pigment, a red pigment, a blue pigment, a yellow pigment, or a black pigment. Only one kind of the pigment may be used, or two or more kinds may be used in combination.
[0131] From the viewpoint of effectively suppressing light leakage, effectively suppressing discoloration, and further improving the conduction reliability of the obtained dimming laminate, the pigment is more preferably an organic pigment, more preferably a black pigment, and even more preferably an organic black pigment.
[0132] Examples of the organic black pigment include anthraquinone pigments, anthraquinone pigments, dianthraquinone pigments, anthrapyrimidine pigments, flavanthrone pigments, diketopyrrolopyrrole pigments, quinacridone pigments, diketopyrrolopyrrole pigments, indigo / thioindigo pigments, pyrenone pigments, perylene pigments, phthalocyanine pigments, halogenated phthalocyanine pigments, indoline pigments, isoindoline pigments, isoindolinone pigments, indanthrone pigments, dioxazine pigments, quinophthalone pigments, nickel azo pigments, metal complex pigments, azo pigments (insoluble azo pigments, soluble azo pigments, high molecular weight azo pigments, and azomethine black pigments), and nigrosine pigments.
[0133] The average particle size of the organic black pigment is preferably 1 nm or more, more preferably 10 nm or more, preferably 500 nm or less, more preferably 300 nm or less, and further preferably 100 nm or less. The average particle size represents the weight average particle size. The average particle size can be measured by a dynamic light scattering method using a light scattering measuring device with a laser as a light source. Examples of the light scattering measuring device include "DLS-6000AL" manufactured by OTSUKA ELECTRONICS.
[0134] From the viewpoint of further suppressing the variation in transmittance of the obtained light-adjusting laminated body, the colorant preferably contains an organic black pigment, titanium black particles, or carbon black particles, and more preferably contains carbon black particles.
[0135] In 100 wt % of the polysiloxane particles, the content of the filler is preferably 0.1 wt % or more, more preferably 0.5 wt % or more, further preferably 1.0 wt % or more, particularly preferably 3.0 wt % or more, preferably 30 wt % or less, more preferably 20 wt % or less, further preferably 15 wt % or less, particularly preferably 10 wt % or less. If the content of the filler is above the lower limit and below the upper limit, the ratio (10% K value at 90°C / 10% K value at 25°C) can be more easily adjusted to the preferred range, so that the deviation of the transmittance of the obtained dimming laminate can be further suppressed, and the damage to the substrate can be further suppressed. It should be noted that when the polysiloxane particles contain two or more fillers, the content of the filler refers to the total content of each filler.
[0136] In 100 wt % of the polysiloxane particles, the content of the colorant is preferably 0.1 wt % or more, more preferably 0.5 wt % or more, further preferably 1.0 wt % or more, particularly preferably 3.0 wt % or more, preferably 30 wt % or less, more preferably 20 wt % or less, further preferably 15 wt % or less, particularly preferably 10 wt % or less. When the content of the colorant is above the lower limit and below the upper limit, the deviation of the transmittance of the obtained dimming laminate can be further suppressed. It should be noted that, when the polysiloxane particles contain two or more colorants, the content of the colorant refers to the total content of each colorant.
[0137] <Other ingredients>
[0138] The polysiloxane particles may contain other components as required. Examples of the other components include polymerization initiators, pigment dispersants, resin particle dispersants, and surfactants. The other components may be used alone or in combination of two or more.
[0139] (Dimmable laminate)
[0140] The light-adjusting laminated body of the present invention comprises a first substrate, a second substrate, and a light-adjusting layer disposed between the first substrate and the second substrate. In the light-adjusting laminated body of the present invention, the light-adjusting layer contains the polysiloxane particles.
[0141] In the dimming stack of the present invention, since it has the above-mentioned structure, the gap between the substrates can be controlled with high accuracy even in a high temperature environment, and the transmittance variation of the obtained dimming stack can be suppressed, thereby suppressing damage to the substrates.
[0142] The dimming stack may be a dimming stack of GHLC (Guest-Host Liquid Crystal), a dimming stack of PDLC (Polymer Dispersed Liquid Crystal), or a dimming stack of SPD (Suspended Particle Device). The dimming stack is preferably a dimming stack of GHLC, SPD or PDLC, more preferably a dimming stack of SPD or PDLC. The dimming stack may not be a liquid crystal display device. The dimming stack may not be a liquid crystal display element.
[0143] Figure 3 This is a cross-sectional view schematically showing a PDL C-type light-adjusting laminated body including the polysiloxane particles according to the first embodiment of the present invention. Figure 4 This is a cross-sectional view schematically showing an SPD-type light-adjusting laminated body including the polysiloxane particles according to the first embodiment of the present invention. Figure 5 2 is a cross-sectional view schematically showing a GHLC-type dimming laminate including polysiloxane particles according to the first embodiment of the present invention. Figure 3 to Figure 5 In the figure, for the convenience of illustration, the size, thickness, shape and addition amount of the light-adjusting layer and the polysiloxane particles are appropriately changed according to the actual size and shape.
[0144] Figure 3 The dimming stack 21 of the PDLC method shown in the figure includes a first substrate 11, a second substrate 12, and a dimming layer 13. The dimming layer 13 is sandwiched between the first substrate 11 and the second substrate 12. The dimming layer 13 is arranged between the first substrate 11 and the second substrate 12. A sealant may also be arranged around the dimming layer 13 between the first substrate 11 and the second substrate 12.
[0145] The light-adjusting layer 13 includes polysiloxane particles 1, liquid crystal capsules 13A and a binder 13B. The liquid crystal capsules 13A are liquid crystal materials. The liquid crystal capsules 13A are dispersed in the binder 13B. The liquid crystal capsules 13A are held in the binder 13B in a capsule shape. The liquid crystal material may be dispersed in the binder in a capsule shape, or the liquid crystal material may be dispersed in the binder as a continuous phase.
[0146] The polysiloxane particles 1 are in contact with the first substrate 11 and the second substrate 12. The polysiloxane particles 1 control the gap between the first substrate 11 and the second substrate 12.
[0147] Electrodes (not shown) are formed on the surface of the first substrate 11 and the surface of the second substrate 12. Examples of the material of the electrodes include indium tin oxide (ITO) and the like. The electrodes are preferably transparent electrodes.
[0148] When no electric field is applied to the PDLC dimming stack 21 , the liquid crystal molecules in the liquid crystal capsule 13A are not uniformly oriented. Therefore, due to the difference in refractive index between the adhesive 13B and the liquid crystal material, incident light is scattered in the adhesive, resulting in an opaque state.
[0149] When an electric field is applied to the PDLC light-adjusting laminate 21, the liquid crystal molecules in the liquid crystal capsule 13A are aligned in a direction parallel to the electric field. In this state, the binder 13B and the liquid crystal material have the same refractive index, so light can pass through and the state becomes transparent.
[0150] Figure 4 The illustrated SPD type dimming laminate 22 includes a first substrate 11, a second substrate 12, and a dimming layer 14. The dimming layer 14 is sandwiched between the first substrate 11 and the second substrate 12. The dimming layer 14 is disposed between the first substrate 11 and the second substrate 12.
[0151] The light-adjusting layer 14 includes silicone particles 1, droplets 14A of a light-adjusting suspension, and a resin matrix 14B. The droplets 14A of the light-adjusting suspension are dispersed in the resin matrix 14B. The droplets 14A of the light-adjusting suspension are held in the resin matrix 14B in a droplet state.
[0152] The droplet 14A of the light adjustment suspension contains a dispersion medium 14Aa and light adjustment particles 14Ab. The light adjustment particles 14Ab are dispersed in the dispersion medium 14Aa.
[0153] The polysiloxane particles 1 are in contact with the first substrate 11 and the second substrate 12. The polysiloxane particles 1 control the gap between the first substrate 11 and the second substrate 12.
[0154] Electrodes (not shown) are formed on the surface of the first substrate 11 and the surface of the second substrate 12. Examples of the material of the electrodes include indium tin oxide (ITO) and the like. The electrodes are preferably transparent electrodes.
[0155] When no electric field is applied to the SPD dimming stack 22 , incident light is absorbed, scattered or reflected by the light regulating particles 14Ab due to the Brownian motion of the light regulating particles 14Ab dispersed in the dispersion medium 14Aa of the droplets 14A constituting the light regulating suspension, and the incident light cannot pass through the dimming layer 14 .
[0156] When an electric field is applied to the SPD light-adjusting laminate 22 , the light-adjusting particles 14Ab are aligned in a direction parallel to the electric field. Therefore, incident light can pass between the aligned light-adjusting particles 14Ab and transmit the light-adjusting layer 14 .
[0157] Figure 5 The dimming stack 23 of the GHLC method shown in the figure includes a first substrate 11, a second substrate 12, and a dimming layer 15. The dimming layer 15 is sandwiched between the first substrate 11 and the second substrate 12. The dimming layer 15 is arranged between the first substrate 11 and the second substrate 12. A sealant may be arranged around the dimming layer 15 between the first substrate 11 and the second substrate 12.
[0158] The light-adjusting layer 15 includes polysiloxane particles 1, a dichroic dye 15A, and a liquid crystal material 15B (liquid crystal). The dichroic dye 15A is dispersed in the liquid crystal material 15B.
[0159] The polysiloxane particles 1 are in contact with the first substrate 11 and the second substrate 12. The polysiloxane particles 1 control the gap between the first substrate 11 and the second substrate 12.
[0160] Electrodes (not shown) are formed on the surface of the first substrate 11 and the surface of the second substrate 12. Examples of the material of the electrodes include indium tin oxide (ITO) and the like. The electrodes are preferably transparent electrodes.
[0161] exist Figure 5 , a state in which an electric field is not applied to the GHLC dimming stack 23 is shown. In the state in which an electric field is not applied, the dichroic dye 15A is oriented in a direction perpendicular to the thickness direction of the GHLC dimming stack 23. In addition, although the orientation is not shown, the liquid crystal material 15B is also arranged in a direction perpendicular to the thickness direction of the GHLC dimming stack 23. When an electric field is applied to the GHLC dimming stack 23, the dichroic dye 15A and the liquid crystal material 15B are arranged in a direction parallel to the electric field, that is, in the thickness direction of the GHLC dimming stack 23. Therefore, the incident light can pass between the arranged dichroic dyes 15A and can transmit the dimming layer 15.
[0162] <Dimming Layer>
[0163] The light-adjusting layer preferably has light-adjusting property. Light-adjusting property refers to a property that visible light transmittance changes depending on whether an electric field is applied, and the amount of incident light can be adjusted. The light-adjusting layer includes the polysiloxane particles.
[0164] (PDLC method)
[0165] The dimming layer preferably further includes a binder and a liquid crystal material dispersed in the binder.
[0166] The liquid crystal material is not particularly limited, and can be any liquid crystal material as long as it has the property of changing its orientation by applying an electric field. The liquid crystal material can be dispersed in the adhesive as a continuous phase, or dispersed in the adhesive in the form of liquid crystal droplets or liquid crystal capsules. Examples of the liquid crystal material include nematic liquid crystals and cholesteric liquid crystals.
[0167] Examples of the material for the nematic liquid crystal include cyanobiphenyls, phenyl esters, azoxybenzenes, fluorinated biphenyls, carbonates, and Schiff bases. The material for the nematic liquid crystal may be used alone or in combination of two or more.
[0168] As the material of the cholesteric liquid crystal, there can be cited nematic liquid crystals or smectic liquid crystals such as steroid cholesterol derivatives, Schiff bases, azos, azoxys, benzoates, biphenyls, terphenyls, cyclohexylcarboxylates, phenylcyclohexanes, biphenylcyclohexanes, pyrimidines, dioxanes, cyclohexylcyclohexane esters, cyclohexylethanes, cyclohexanes, tolans, alkenyls, stilbenes, condensed polycyclics, and materials in which chiral components composed of optically active materials such as Schiff bases, azos, esters, and biphenyls are added to their mixed liquid crystals, etc. The material of the cholesteric liquid crystal can be used alone or in combination of two or more.
[0169] The adhesive holds the liquid crystal material and inhibits the flow of the liquid crystal material. The adhesive is not particularly limited. The adhesive is preferably insoluble in the liquid crystal material, has a strength that can withstand external forces, and has high transmittance to reflected light and incident light. As the material of the adhesive, water-soluble polymer materials such as gelatin, polyvinyl alcohol, cellulose derivatives, polyacrylic polymers, ethyleneimine, polyethylene oxide, polyacrylamide, polystyrene sulfonate, polyamidine, isoprene sulfonic acid polymers, and materials that can be emulsified in water such as fluororesins, polysiloxane resins, acrylic resins, polyurethane resins, epoxy resins, etc. can be cited. The material of the adhesive can be used alone or in combination of two or more.
[0170] The adhesive is preferably cross-linked by a cross-linking agent. The cross-linking agent is not particularly limited. The cross-linking agent is preferably a cross-linking agent that forms cross-links between the adhesives and can make the adhesive hard, difficult to dissolve or insoluble. As the cross-linking agent, acetaldehyde, glutaraldehyde, glyoxal, potassium alum hydrate of a polyvalent metal salt compound, adipic acid dihydrazide, melamine formaldehyde oligomer, ethylene glycol diglycidyl ether, polyamide epichlorohydrin and polycarbodiimide can be cited. The cross-linking agent can be used alone or in combination of two or more.
[0171] (SPD method)
[0172] The dimming layer preferably further comprises a resin matrix and a light-adjusting suspension dispersed in the resin matrix.
[0173] The light-modulating suspension includes a dispersion medium and light-modulating particles dispersed in the dispersion medium.
[0174] As the light regulating particles, carbon materials such as polyiodide and carbon black, metal materials such as copper, nickel, iron, cobalt, chromium, titanium, aluminum, and inorganic compound materials such as silicon nitride, titanium nitride, and aluminum oxide can be cited. In addition, particles of these materials covered by polymers can also be used. The light regulating particles can be used alone or in combination of two or more.
[0175] The dispersion medium disperses the light regulating particles in a flowable state. The dispersion medium is preferably: selectively attached to the light regulating particles, coating the light regulating particles, and acting in a manner that the light regulating particles move toward the droplet phase after phase separation when phase separation occurs with the resin matrix, and has no conductivity and no affinity with the resin matrix. In addition, the dispersion medium is preferably a liquid copolymer having a refractive index similar to that of the resin matrix when a dimming laminate is made. As the liquid copolymer, it is preferably a (meth)acrylate oligomer having a fluorine group or a hydroxyl group, and more preferably a (meth)acrylate oligomer having a fluorine group and a hydroxyl group. If such a copolymer is used, the monomer units of the fluorine group or the hydroxyl group are oriented toward the light regulating particles, and the remaining monomer units stabilize the droplets of the light regulating suspension in the resin matrix. Therefore, the light regulating particles are easily dispersed in the light regulating suspension, and the light regulating particles are easily guided into the phase-separated droplets when phase separation occurs with the resin matrix.
[0176] Examples of the (meth)acrylate oligomer having a fluorine group or a hydroxyl group include: 2,2,2-trifluoroethyl methacrylate / butyl acrylate / 2-hydroxyethyl acrylate copolymer, 3,5,5-trimethylhexyl acrylate / 2-hydroxypropyl acrylate / fumaric acid copolymer, butyl acrylate / 2-hydroxyethyl acrylate copolymer, 2,2,3,3-tetrafluoropropyl acrylate / butyl acrylate / 2-hydroxyethyl acrylate copolymer, 1H,1H,5H-octafluoropentyl acrylate / butyl acrylate / 2-hydroxyethyl acrylate copolymer, 1H acrylate , 1H,2H,2H-heptadecafluorodecyl ester / butyl acrylate / 2-hydroxyethyl acrylate copolymer, 2,2,2-trifluoroethyl methacrylate / butyl acrylate / 2-hydroxyethyl acrylate copolymer, 2,2,3,3-tetrafluoropropyl methacrylate / butyl acrylate / 2-hydroxyethyl acrylate copolymer, 1H,1H,5H-octafluoropentyl methacrylate / butyl acrylate / 2-hydroxyethyl acrylate copolymer, and 1H,1H,2H,2H-heptadecafluorodecyl methacrylate / butyl acrylate / 2-hydroxyethyl acrylate copolymer. In addition, these (meth)acrylate oligomers preferably have both a fluorine group and a hydroxyl group.
[0177] The weight average molecular weight of the (meth)acrylate oligomer is preferably 1,000 or more, more preferably 2,000 or more, and is preferably 20,000 or less, more preferably 10,000 or less.
[0178] The light-adjusting layer may be prepared using the resin material used to form the resin matrix and the light-adjusting suspension.
[0179] The resin material is preferably a resin material that is cured by irradiation with energy rays. As the resin material that is cured by irradiation with energy rays, there can be mentioned: a polymer composition containing a photopolymerization initiator and a polymer compound that is cured by energy rays such as ultraviolet rays, visible rays, and electron beams. As the polymer composition, there can be mentioned: a polymer composition containing a polymerizable monomer having an ethylenically unsaturated group and a photopolymerization initiator. As the polymerizable monomer having an ethylenically unsaturated group, there can be mentioned non-crosslinking monomers and crosslinking monomers.
[0180] Examples of the non-crosslinking monomer include: styrene monomers such as styrene, α-methylstyrene, and chlorostyrene as vinyl compounds; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, 1,4-butanediol divinyl ether, cyclohexanedimethanol divinyl ether, and diethylene glycol divinyl ether; vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate acid vinyl ester compounds; halogen-containing monomers such as vinyl chloride and vinyl fluoride; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate as (meth)acrylic compounds; 2-ethylhexyl (meth)acrylate, and 1,4-butylene glycol divinyl ether; and 1,4-butylene glycol divinyl ether. (Meth)acrylate alkyl ester compounds such as laurate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate; (meth)acrylate compounds containing oxygen atoms such as 2-hydroxyethyl (meth)acrylate, glyceryl (meth)acrylate, polyoxyethylene (meth)acrylate, glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; trifluoromethyl (meth)acrylate; halogen-containing (meth)acrylate compounds such as pentafluoroethyl (meth)acrylate; olefin compounds such as diisobutylene, isobutylene, linear olefins, ethylene, propylene, etc. as α-olefin compounds; isoprene, butadiene, etc. as conjugated diene compounds.
[0181] Examples of the crosslinking monomer include: vinyl monomers such as divinylbenzene, 1,4-divinyloxybutane, and divinyl sulfone as vinyl compounds; tetramethylolmethane tetra(meth)acrylate as (meth)acrylic compounds; polytetramethylene glycol diacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, polyethylene glycol di(meth)acrylate; as the allyl compound, triallyl (iso)cyanurate, triallyl trimellitate, diallyl phthalate, diallyl acrylamide, diallyl ether; as the silane compound, tetramethoxysilane, tetraethoxysilane, triethylsilane, tert-butyldimethylsilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, isopropyltrimethoxysilane, isobutyltrimethoxysilane, cyclohexyltrimethoxysilane, n-hexyltrimethoxysilane Silane alkoxide compounds such as methoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, trimethoxysilylstyrene, γ-(methyl)acryloxypropyltrimethoxysilane, 1,3-divinyltetramethyldisiloxane, methylphenyldimethoxysilane, diphenyldimethoxysilane; vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, dimethoxyethylvinylsilane, diethoxymethylvinylsilane, diethoxyethylvinylsilane, ethylmethyldivinylsilane, methylvinyl Silane alcohol salts containing polymerizable double bonds such as dimethoxysilane, ethylvinyldimethoxysilane, methylvinyldiethoxysilane, ethylvinyldiethoxysilane, p-phenylvinyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane; cyclic siloxanes such as decamethylcyclopentasiloxane; modified (reactive) silicone oils such as single-end modified silicone oil, double-end silicone oil, and side chain silicone oil; carboxyl-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride, etc.
[0182] Examples of the photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-(4-(2-hydroxyethoxy)phenyl)-2-hydroxy-2-methyl-1-propane-1-one, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-hydroxy-2-methyl-1-phenylpropane-1-one, and (1-hydroxycyclohexyl)phenyl ketone.
[0183] The resin material may include an organic solvent-soluble resin, a thermoplastic resin, poly(meth)acrylic acid, etc. In addition, the resin material may include various additives such as an anti-coloring agent, an antioxidant, and an adhesion-imparting agent, and may also include a solvent.
[0184] (GHLC method)
[0185] The dimming layer preferably comprises a dichroic pigment and a liquid crystal material.
[0186] Examples of the liquid crystal material include the nematic liquid crystal and cholesteric liquid crystal described above.
[0187] The dichroic pigment is, for example, a pigment that appears colored from a certain direction and appears colorless from a direction perpendicular to the certain direction. The dichroic pigment is preferably a substance that can absorb at least a portion of light in the visible light region (e.g., a wavelength of 400nm to 700nm), and more preferably a substance that can anisotropically absorb at least a portion of light in the visible light region. As the dichroic pigment, azo pigments and anthraquinone pigments can be cited. The dichroic pigment is preferably a dye.
[0188] <First Base Material and Second Base Material>
[0189] The first substrate is preferably a transparent substrate. The second substrate is preferably a transparent substrate. The transparent substrate is, for example, a substrate having light transmittance (light-transmitting substrate). For example, light is transmitted from one side of the transparent substrate to the other side through the transparent substrate. For example, when a substance located on the other side is visually observed from one side of the transparent substrate through the transparent substrate, the substance can be visually confirmed. Transparency, for example, also includes translucency. The transparent substrate can be colorless and transparent, or can be colored and transparent.
[0190] The materials of the first substrate and the second substrate are not particularly limited. The material of the first substrate and the material of the second substrate may be the same or different. As the materials of the first substrate and the second substrate, glass and resin film etc. may be cited. As the glass, soda lime glass, lead glass, borosilicate glass, and glass of various compositions in other uses for general construction, as well as functional glass such as heat-reflecting glass, heat-absorbing glass and tempered glass may be cited. As the resin film, polyester films such as polyethylene terephthalate, polyolefin films such as polypropylene, and resin films such as acrylic resin films may be cited. From the aspects of excellent transparency, formability, adhesion, processability, etc., the first substrate and the second substrate are preferably resin substrates, more preferably resin films, and further preferably polyethylene terephthalate (PET) films.
[0191] The first substrate and the second substrate preferably include a substrate body and a conductive film formed on the surface of the substrate body so as to be able to apply an electric field for light modulation. Examples of the conductive film include indium tin oxide (ITO), SnO2, and In2O3. The conductive film is preferably a transparent conductive film.
[0192] From the viewpoint of further improving the visibility of the dimming laminate, the visible light transmittance of the first substrate and the second substrate is preferably 75% or more, more preferably 80% or more. The visible light transmittance of the first substrate and the second substrate may be 100% or less, or 99% or less.
[0193] The visible light transmittance of the first substrate and the second substrate can be measured by spectrometry or the like in accordance with ISO13837:2008.
[0194] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0195] Prepare the following materials.
[0196] (Material of polysiloxane particles):
[0197] Polysiloxane resin A (polysiloxane modified with acrylic acid at both ends, "X-22-2445" manufactured by Shin-Etsu Chemical Co., Ltd., number of repeating structural units: 40)
[0198] Polysiloxane resin B (polysiloxane modified with methacrylic acid at both ends, "X-22-164A" manufactured by Shin-Etsu Chemical Co., Ltd., number of repeating structural units: 20)
[0199] Polysiloxane resin C (polysiloxane modified with methacrylic acid at both ends, "X-22-164" manufactured by Shin-Etsu Chemical Co., Ltd., number of repeating structural units: 10)
[0200] Divinylbenzene
[0201] (filler):
[0202] Carbon black particles (inorganic particles, particle size 20μm)
[0203] Titanium black particles (inorganic particles, particle size 80μm)
[0204] (1) Preparation of polysiloxane particles
[0205] (Example 1)
[0206] Add 5 parts by weight of carbon black particles to 95 parts by weight of polysiloxane resin A and stir to obtain a monomer solution in which carbon black particles are dispersed, then add 7 parts by weight of a free radical polymerization initiator (tert-butyl peroxy 2-ethylhexanoate, "PERBUTYL O" manufactured by NOF Corporation) and stir until uniform to obtain a monomer mixture. Put 200 parts by weight of a 2.5% by weight aqueous solution obtained by dissolving polyvinyl alcohol having a molecular weight of about 2000 in pure water into a reactor. Add the obtained monomer mixture thereto, and adjust the particle size by stirring so that the droplets of the monomer become a given particle size. Then, heat at 90°C for 9 hours to perform a polymerization reaction of the monomer droplets to obtain particles. After washing the obtained particles 3 times with hot water and acetone, respectively, perform a classification operation to recover the polysiloxane particles.
[0207] (Examples 2 to 11 and Comparative Examples 1 to 4)
[0208] Polysiloxane particles were prepared in the same manner as in Example 1 except that the filler and the material and content (weight %) of the polysiloxane particle main body were changed as shown in Tables 1 to 4, and the average particle size of the polysiloxane particles was set as shown in Tables 1 to 4. In Table 4, Comparative Examples 3 and 4 not containing a polysiloxane resin are not polysiloxane particles, but are described in the columns of "polysiloxane particle main body" and "polysiloxane particles" for convenience.
[0209] (2) Preparation of dimming laminate
[0210] SPD dimming stack:
[0211] A dimming film having a known SPD layer was prepared by dispersing 5 wt % of the obtained polysiloxane particles between two PET films on which transparent and conductive ITO was deposited. A SPD dimming laminate was prepared by sandwiching the dimming film between two transparent glasses.
[0212] PDLC dimming laminate:
[0213] A dimming film having a known PDLC layer was prepared by dispersing 5 wt % of the obtained polysiloxane particles between two PET films on which transparent and conductive ITO was deposited. A PDLC dimming laminate was prepared by sandwiching the dimming film between two transparent glasses.
[0214] (evaluate)
[0215] (1) Average particle size
[0216] About 100,000 particles of the obtained polysiloxane particles were measured using a particle size distribution analyzer ("Multisizer 4" manufactured by Beckman Coulter Inc.), and the average particle size was measured.
[0217] (2) CV value of particle size
[0218] The CV value of the particle size of the obtained polysiloxane particles was calculated by the above method.
[0219] (3) Visible light transmittance
[0220] The visible light transmittance of the obtained polysiloxane particles was calculated by the above-mentioned method.
[0221] (4) 10% K value at 25°C and 90°C
[0222] The 10% K value of the obtained polysiloxane particles at 25°C and 90°C was measured by the above method using "FISCHER SCOPE H-100" manufactured by FISCHER. The ratio (10% K value at 90°C / 10% K value at 25°C) was determined.
[0223] (5) Compression recovery rate at 25°C
[0224] The obtained polysiloxane particles were measured for compression recovery at 25° C. by the above-mentioned method using “FISCHER SCOPE H-100” manufactured by FISCHER.
[0225] (6) Gap control at 90°C
[0226] The obtained dimming laminate was heated at 90° C. for 3 hours, and the maximum and minimum values of the distance between the substrates (PET films) were measured. The gap controllability at 90° C. was determined according to the following criteria.
[0227] [Criteria for determining gap controllability at 90°C]
[0228] ○○○: The maximum distance between substrates is less than 1.05 times the minimum distance
[0229] ○○: The maximum value of the distance between the substrates is 1.05 times or more and less than 1.10 times the minimum value
[0230] ○: The maximum value of the distance between the substrates is 1.10 times or more and less than 1.15 times the minimum value
[0231] ×: The maximum value of the distance between the substrates is 1.15 times or more the minimum value
[0232] (7) Suppression of Transmittance Variation of Light Regulating Laminated Body
[0233] The obtained dimming laminate was irradiated with light of wavelength 380nm to 780nm according to JIS S3107, and the visible light transmittance (%) (hereinafter referred to as transmittance) was measured at a total of 5 points including 4 corners and the center, and the maximum and minimum values of the transmittance were obtained, and the difference was obtained. The transmittance deviation suppression of the dimming laminate was determined according to the following criteria.
[0234] [Criteria for judging the deviation of transmittance of the light-adjusting laminate]
[0235] ○○○: The difference between the maximum and minimum transmittance is less than 5%
[0236] ○○: The difference between the maximum and minimum values of transmittance is 5% or more and less than 10%
[0237] ○: The difference between the maximum and minimum values of transmittance is 10% or more and less than 20%
[0238] ×: The difference between the maximum and minimum transmittance is 20% or more
[0239] (8) Damage inhibition of substrate
[0240] The obtained dimming laminate was subjected to a vibration test under the following conditions. The dimming laminate after the vibration test was counted using an optical microscope (observation magnification 50 times) on the surface of the polysiloxane particles of the substrate (PET film) per 150 mm 2 The damage resistance of the substrate was determined according to the following criteria.
[0241] (Conditions of vibration test)
[0242] Device used: VS3000 / SA3M (manufactured by IMV)
[0243] Vibration frequency: 2000Hz
[0244] Acceleration: 30.8m / s 2
[0245] Test direction and test time: 8 hours in horizontal direction, 8 hours in vertical direction [Criteria for judging the damage inhibition of the substrate]
[0246] ○○: The number of scars is 0
[0247] ○: The number of scars is 1 or more and 3 or less
[0248] ×: The number of scars is 4 or more
[0249] The composition of the polysiloxane particles and the results are shown in Tables 1 to 4 below.
[0250] [Table 1]
[0251]
[0252] [Table 2]
[0253]
[0254] [Table 3]
[0255]
[0256] [Table 4]
[0257]
[0258] Explanation of symbols
[0259] 1. 1A…Polysiloxane particles
[0260] 2…Polysiloxane particle main body
[0261] 3. 3A…filler
[0262] 11…First substrate
[0263] 12…Second substrate
[0264] 13, 14, 15…dimming layer
[0265] 13A…Liquid crystal capsule
[0266] 13B…Adhesive
[0267] 14A… Droplets of light-regulated suspensions
[0268] 14Aa…Dispersion medium
[0269] 14Ab…Light-regulated particles
[0270] 14B…resin matrix
[0271] 15A…Dichroic pigment
[0272] 15B…Liquid crystal material
[0273] 21…PDLC-based dimming laminate
[0274] 22…SPD dimming laminate
[0275] 23…GHLC dimming laminate
Claims
1. A polysiloxane particle comprising a polysiloxane particle body and a plurality of fillers, At least one of the plurality of fillers is present inside the polysiloxane particle body, The ratio of the 10% K value of the polysiloxane particles at 90° C. to the 10% K value at 25° C. is 0.90 or more.
2. The polysiloxane particles according to claim 1, wherein The 10% K value at 25°C is 2000 N / mm 2 the following.
3. The polysiloxane particles according to claim 1 or 2, wherein The 10% K value at 90°C is 1800 N / mm 2 the following. The polysiloxane particles according to any one of claims 1 to 3, which have a compression recovery rate at 25°C of 91% or less. The polysiloxane particles according to any one of claims 1 to 4, which have a particle size of 30 μm or less. 6 . The polysiloxane particles according to claim 1 , wherein the CV value of the particle size is 15% or less. 7 . The polysiloxane particles according to claim 1 , which have a visible light transmittance of 10% or less.
8. The polysiloxane particles according to any one of claims 1 to 7, wherein The filler is a colorant.
9. The polysiloxane particles according to claim 8, wherein The colorant is inorganic particles, pigment or dye.
10. The polysiloxane particles according to claim 8 or 9, wherein The colorant is a white colorant or a black colorant.
11. The polysiloxane particles according to any one of claims 1 to 10, wherein The content of the filler in 100 wt % of the polysiloxane particles is 0.1 wt % or more and 30 wt % or less.
12. The polysiloxane particles according to claim 11, wherein The content of the filler in 100% by weight of the polysiloxane particles is 3.0% by weight or more and 10% by weight or less.
13. A dimming laminate, comprising: The first substrate, a second substrate, and A light-adjusting layer disposed between the first substrate and the second substrate, the light-adjusting layer comprising the polysiloxane particles according to any one of claims 1 to 12.
Citation Information
Patent Citations
polymer particles
JP2022079565A